Cellular metabolites modulate in vivo signaling of Arabidopsis cryptochrome-1 - El-Esawi, Mohamed (Plant Signal Behav, 2015)
Cryptochromes are blue-light absorbing flavoproteins with multiple signaling roles. In plants, cryptochrome (cry1, cry2) biological activity has been linked to flavin photoreduction via an electron transport chain to the protein surface comprising 3 evolutionarily conserved tryptophan residues known as the ‘Trp triad.’ Mutation of any of the Trp triad residues abolishes photoreduction in isolated cryptochrome protein in vitro and therefore had been suggested as essential for electron transfer to the flavin. However, photoreduction of the flavin in Arabidopsis cry2 proteins occurs in vivo even with mutations in the Trp triad, indicating the existence of alternative electron transfer pathways to the flavin. These pathways are potentiated by metabolites in the intracellular environment including ATP, ADP, AMP, and NADH. In the present work we extend these observations to Arabidopsis cryptochrome 1 and demonstrate that Trp triad substitution mutants at W400F and W324F positions which are not photoreduced in vitro can be photoreduced in whole cell extracts, albeit with reduced efficiency. We further show that the flavin signaling state (FADH°) is stabilized in an in vivo context. These data illustrate that in vivo modulation by metabolites in the cellular environment may play an important role in cryptochrome signaling, and are discussed with respect to possible effects on the conformation of the C-terminal domain to generate the biologically active conformational state.